Physical Exercise and Executive Function in the Pediatric Overweight and Obesity Population: A Systematic Review Protocol - Arellano-Roco, C (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
Background: Executive function is often altered in overweight/obese children and adolescents, which has a negative impact on their learning and daily life. Furthermore, research has shown the benefits of physical exercise in improving cognitive performance. This protocol aims to define in a detailed and structured manner the procedures that will be conducted for the development of a systematic review of the literature aimed at evaluating the effects of physical exercise on the executive functions of children and adolescents (≤18 years) with overweight/obesity in comparison with peers in control groups. Methods: The Web of Science, PubMed, Scopus, and EBSCO databases will be searched for longitudinal studies that have at least one experimental and one control group using pre- and post-intervention measures of executive function, including working memory, inhibition, and cognitive flexibility in the pediatric population who are overweight or obese. The risk of bias and certainty of evidence will be assessed using Cochrane RoB2 and GRADE, respectively. Furthermore, Der Simonian–Laird’s random effects model will be employed for meta-analyses. The effect sizes will be calculated with 95% confidence intervals, and p values < 0.05 indicate statistical significance for each dimension of executive function in the different groups before and after the intervention. Discussion: The results of this review may be useful for education and health professionals to design treatment plans for overweight/obese children and adolescents, offering potential benefits related to the learning and cognitive abilities of this population. PROSPERO registration number: CRD42023391420. © 2024 by the authors.